Fetal surgery and stem cell therapy for meningomyelocele. Issue 2 (April 2020) - Hii, Ling-Yien; Sung, Chen-Ai; Shaw, Steven W.
Abstract : Purpose of review: To review the advance of maternal–fetal surgery, the research of stem cell transplantation and tissue engineering in prenatal management of fetal meningomyelocele (fMMC). Recent findings: Advance in the imaging study provides more accurate assessment of fMMC in utero. Prenatal maternal–fetal surgery in fMMC demonstrates favourable postnatal outcome. Minimally invasive fetal surgery minimizes uterine wall disruption. Endoscopic fetal surgery is performed via laparotomy-assisted or entirely percutaneous approach. The postnatal outcome for open and endoscopic fetal surgery shares no difference. Single layer closure during repair of fMMC is preferred to reduce postnatal surgical intervention. All maternal–fetal surgeries impose anesthetic and obstetric risk to pregnant woman. Ruptured of membrane and preterm delivery are common complications. Trans-amniotic stem cell therapy (TRASCET) showed potential tissue regeneration in animal models. Fetal tissue engineering with growth factors and dura substitutes with biosynthetic materials promote spinal cord regeneration. This will overcome the challenge of closure in large fMMC. Planning of the maternal–fetal surgery should adhere to ethical framework to minimize morbidity to both fetus and mother. Summary: Combination of endoscopic fetal surgery with TRASCET or tissue engineering will be a new vision to achieve to improve the outcome of prenatal intervention in fMMC.